2008
DOI: 10.1016/j.molcel.2008.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Mediator-Dependent Recruitment of TFIIH Modules in Preinitiation Complex

Abstract: In vitro, without Mediator, the association of general transcription factors (GTF) and RNA polymerase II (Pol II) in preinitiation complexes (PIC) occurs in an orderly fashion. In this work, we explore the in vivo function of Mediator in GTF recruitment to PIC. A direct interaction between Med11 Mediator head subunit and Rad3 TFIIH subunit was identified. We explored the significance of this interaction and those of Med11 with head module subunits Med17 and Med22 and found that impairing these interactions cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
149
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(157 citation statements)
references
References 59 publications
8
149
0
Order By: Relevance
“…Our structural and biochemical data along with relevant previous observations 12,17,23,24 suggests an interaction of the Pol II CTD, the Mediator Head module and TFIIH: First, mutation of Thr47 to Ala in Med11 affects the interaction of TFIIH with the Head module in vivo, resulting in a reduction of Pol II CTD Ser5 phosphorylation 17 . Thr47 of Med11 is located near the center of the two symmetrical long helical bundles of the Neck, which thus could constitute the docking surface for TFIIH ( Figure 4b)( Supplementary Fig.…”
Section: Derivatives (Supplementary Text 3)supporting
confidence: 72%
See 1 more Smart Citation
“…Our structural and biochemical data along with relevant previous observations 12,17,23,24 suggests an interaction of the Pol II CTD, the Mediator Head module and TFIIH: First, mutation of Thr47 to Ala in Med11 affects the interaction of TFIIH with the Head module in vivo, resulting in a reduction of Pol II CTD Ser5 phosphorylation 17 . Thr47 of Med11 is located near the center of the two symmetrical long helical bundles of the Neck, which thus could constitute the docking surface for TFIIH ( Figure 4b)( Supplementary Fig.…”
Section: Derivatives (Supplementary Text 3)supporting
confidence: 72%
“…First, the Med18 loop region formed by residues 78-97 interacts with the Med17 CTH of the Fixed jaw domain ( Figure 3a, 3b). Second, the electron density corresponding to the N-terminus of the Med11 subunit (residues [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] indicates an interaction with Med18 (residues 17-27 and 281-289) ( Figure 3c, 3d). The assignment of Med11 residues 1-20 was complicated by the substitution of Met17 to Ser17 (see Methods), and thus an unambiguous sequence marker is lacking.…”
Section: Derivatives (Supplementary Text 3)mentioning
confidence: 99%
“…In addition to its association with active genes, Mediator has been reported to be present at some inactive gene promoters (26) and at nontranscribed regions of the yeast genome (30). To analyze Mediator presence on inactive genes, we used ChIP to monitor Srb5 and Rgr1 association with the SPO13 and PLM2 …”
Section: Mediator Associates Specifically With Several Constitutivelymentioning
confidence: 99%
“…Recently, we identified a direct interaction between the Med17 Mediator subunit and the Rpb3 Pol II subunit required for global Pol II transcription in vivo (Soutourina et al 2011). Previously, we showed that a direct contact between the Med11 subunit of Mediator and the Rad3 subunit of TFIIH is essential for the recruitment of the GTF to the PIC independently of Pol II (Esnault et al 2008). In addition to the crucial role of Mediator as a link between activators and the basal transcription machinery, recent studies suggest broader Mediator transcriptional functions, notably in the post-recruitment steps of transcription (Wang et al 2005;Takahashi et al 2011) and in DNA looping between the enhancers and promoters through a functional connection with cohesin (Kagey et al 2010).…”
mentioning
confidence: 99%